“Adhesions after abdominal, pelvic and intra-uterine surgery and their prevention” - Wallwiener, Markus (Gynecological surgery, 2012)
We here present the full text of a patient leaflet we have designed, and routinely use, to provide preoperative education about adhesions to patients undergoing open or laparoscopic gynaecological surgery. The leaflet presents appropriate, patient-orientated information on the nature of adhesions, their causes and the health risks they may involve as well as on adhesiolysis and modern methods of adhesion prevention. As adhesion formation is not specific to gynaecological surgery, the leaflet can also be adapted for the purposes of general abdominal surgery.
Published online: 16 August 2012
Gesehen am 22.06.2018